2011
DOI: 10.1590/s0102-09352011000100029
|View full text |Cite
|
Sign up to set email alerts
|

Cultivares de trigo duplo propósito submetidos ao manejo nitrogenado e a regimes de corte

Abstract: Cultivares de trigo duplo propósito submetidos ao manejo nitrogenado e a regimes de corte [Dual- RESUMOAvaliaram-se a produção e a qualidade da forragem em cultivares de trigo duplo propósito submetidos a doses de nitrogênio e a regimes de corte. O delineamento experimental foi o de blocos ao acaso com três repetições. Os tratamentos constituíram-se de quatro cultivares de trigo duplo propósito − BRS Figueira, BRS Umbu, BRS Guatambu e BRS Tarumã −, cinco doses de nitrogênio − 0, 45, 90, 135 e 180kg ha -1 − e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 9 publications
2
9
1
3
Order By: Relevance
“…These results are related to changes in the forage sward as the length of the grazing season increased, including the decrease of the leaf:stem ratio and more lignified cell walls. Similar changes were reported by Hastenpflug et al (2011).…”
Section: Resultssupporting
confidence: 90%
“…These results are related to changes in the forage sward as the length of the grazing season increased, including the decrease of the leaf:stem ratio and more lignified cell walls. Similar changes were reported by Hastenpflug et al (2011).…”
Section: Resultssupporting
confidence: 90%
“…Hastenpflug et al (2011) observed a similar result to this work regarding the average crude protein content for the cultivar BRS Tarumã and linear increases up to the nitrogen rate of 90 and 120 kg ha -1 in the forage dry matter production and crude protein content with 1 cut and 2 cuts, respectively. It should be noted that in the present study, the nitrogen rates evaluated were higher (80 to 240 kg ha -1 ) and the lowest dose was sufficient for the cultivar to reach maximum forage and crude protein yield.…”
Section: Resultssupporting
confidence: 87%
“…Another aspect related to the regrowth and tillering ability is the nutritional status of the plant, especially with regard to nitrogen. In dual-purpose wheat, higher nitrogen doses can be used to increase forage and grain yield without presenting the risk of lodging due to the size reduction caused by cuts (Hastenpflug et al, 2011). Wheat grain yield is highly related to nitrogen management (Sangoi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FONTANELLI (2007) destaca que N é importante para a rebrota rápida da planta após a desfolha, sendo determinante para reduzir o tempo entre pastejos sucessivos. HASTENPFLUG et al (2011) demonstraram que materiais de trigo para duplo propósito apresentam resposta direta à aplicação de N quando se trata de produção de biomassa.…”
Section: Introductionunclassified